THOROUGH FORENSIC MEDICAL ANALYSIS OF EYE INJURIES IN LIVING INDIVIDUALS - Akhrarov Anvar Adilovich; Roziyev Shahzod Murod Ogli; Ganieva Nilufar Khamraevna (Western European Studies, 2025)
The article is devoted to a comprehensive forensic medical characterization of ocular injuries in living individuals. Modern approaches to the classification of ophthalmic trauma are examined, including etiological, mechanical, and anatomical-topographical criteria that allow for a more precise determination of injury patterns and their pathogenetic features. The mechanisms of formation of various types of injuries—from blunt and penetrating to combined and blast-related—are analyzed in detail, which is essential for reconstructing the circumstances of injury and for accurate expert interpretation.Particular attention is given to the diagnostic capabilities of contemporary imaging technologies, such as optical coherence tomography, ocular ultrasonography, and orbital computed tomography. These methods provide high accuracy in detecting subtle, minimally expressed, and deep structural alterations that remain inaccessible during traditional clinical examination. Criteria for determining the degree of harm to health are presented, based on a comprehensive assessment of functional impairment, long-term consequences, and the risk of irreversible loss of visual functions. The pivotal role of commissioned (panel) forensic medical examinations in complex, controversial, iatrogenic, and conflict situations—where multidisciplinary analysis is required—is emphasized.The findings contribute to the improvement of expert assessment algorithms and promote the unification of approaches to evaluating ocular trauma in contemporary forensic medical practice
Keywords: forensic medicine; ocular trauma; eye injury